Spatial and temporal distributions of radiation balance components over Delhi - DAS, Yashvant; PADMANABHAMURTY, Bamapati; MURTY, Ayapilla Satya Narayana (Contributions to Geophysics and Geodesy, 2009)
The study area Delhi was divided according to land-use and the eﬀect of urbanization on the spatial and temporal variations. Incoming shortwave (K↓), albedo (α), incoming longwave (L↓), outgoing longwave (L↑) and net radiation (Q*) were individually studied at ﬁve representative sites (Industrial, Commercial, Residential, Rural and Forest), for the winter and summer seasons. It was found that K↓ was higher in the rural areas with clearer skies and unpolluted atmosphere compared to congested and polluted urban areas. L↓ was higher in the industrial and commercial areas compared to their rural counterparts. Concrete surfaces of urban areas showed lower L↑ unlike the moist rural surfaces. Industrial and commercial areas showed lower α, whereas Q* was higher compared to other areas. However, on an average value of radiation balance components was more than double during summer as compared to winter.